Analysis of Agropreneurship Potential in the Middle of the COVID-19 Pandemic in Kupang City - Rolland E. Fanggidae; Ni Putu Nursiani; I Wayan Mudita (Jurnal Ilmiah Akuntansi, 2023)
This study examines agropreneurship in Kupang City and adjacent areas during the COVID-19 pandemic. The author uses qualitative descriptive methodologies to observe, interview, and document ten local agropreneurs. Newspaper, social media, and YouTube data supplemented the investigation. The results demonstrate that agropreneurs have product quality, reliable output, experience and love of farming, natural resource potential, and commercial and agricultural infrastructure. Agropreneurs benefit from rising demand for fresh veggies, close marketing networks, and reliable business even in times of crisis. However, this sector faces several weaknesses and threats, including inadequate farming equipment, limited capital, a lack of guidance for agropreneurs, limited land, and limited market information, as well as a lack of supporting institutions, high costs, competition, and PSBB-induced market decline. This research helps agropreneurs during crises like the COVID-19 pandemic understand entrepreneurship in Kupang City and the surrounding area. Results may vary by location and circumstance.